The Effect of Health Education on the Prevention of Musculoskeletal Disorders towards Knowledge, Attitudes and Healthy Behaviors of Adolescents in Purwokerto - Hikmi Muharromah Pratiwi; Desiyani Nani (Journal of Bionursing, 2023)
Background: COVID-19 pandemic occurred over the past two years remains several health problems in adolescent, especially musculoskeletal disorders due to inadequate physical activity and body’s posture during activities at home which does not pay attention to ergonomic principles in the long term. Objective: To identify the effect of health education on ergonomic posture and healthy lifestyle on knowledge, attitudes, physical activity and nutritional patterns of adolescents in order to prevent musculoskeletal disorders (MSDs). Methods: This study involved 26 students of a senior high school and used a pre-post-test design without a control group. Data collection with a questionnaire was measured before and after health education. The variables measured include knowledge, attitudes and behavior related to nutrition, knowledge and attitudes about ergonomics and MSDs, knowledge of physical activities and sports. Results: Health education had a significant effect on the level of adolescent’s knowledge related to musculoskeletal nutrition (p = 0.006) and the behavior of increasing nutritional intake for musculoskeletal nutrition (p = 0.015), but had no effect on increasing adolescent knowledge regarding ergonomics (p = 0.687) and physical activity for the prevention of musculoskeletal disorders (p = 1.00). Conclusion: Health education is effective in increasing knowledge and behavior related to musculoskeletal nutrition. Health education innovations are needed to improve attitudes and behavior related to ergonomics and physical activity in adolescents for the prevention of musculoskeletal disorders